Profil Nabi Daniel sebagai Misionaris dan Relevansinya bagi Misi Kaum Profesional - Debbie Yohanna Refialy (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2021)
Abstract: Israel is the nation which was chosen by God to be His people with a purpose that is through Israel, all nations in the world will be a blessing (Genesis 12:1-3). In the long history, Israel didn’t give good influence, but was contaminated with the living and religious pattern of the wicked nations around. The consequence that Israel got was the punishment from God which was the exile to Babylon. The prophet Daniel was one who existed in Babylon. The status as a captivity did not impede Daniel to show his identity as God’s people. Even though he had task as the state officer, but he still did his task as God’s witness and gave impact widely. So functionally, prophet Daniel showed his role as missionary in the land of captivity. Daniel’s deed can be an example for the professional to do God’s mission in each field.